2022
DOI: 10.1083/jcb.202207097
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cells suppress macrophage-mediated corpse removal via upregulation of the CD47-QPCT/L axis

Abstract: Progressive accrual of senescent cells in aging and chronic diseases is associated with detrimental effects in tissue homeostasis. We found that senescent fibroblasts and epithelia were not only refractory to macrophage-mediated engulfment and removal, but they also paralyzed the ability of macrophages to remove bystander apoptotic corpses. Senescent cell-mediated efferocytosis suppression (SCES) was independent of the senescence-associated secretory phenotype (SASP) but instead required direct contact between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…[ 40 ] Besides, a previous report also suggested that senescent cells could disable the efferocytosis function of macrophages to enable their coexistence within the tissue milieu. [ 41 ] Therefore, we could propose that crosstalk between senescent cells and pyroptotic macrophages might result in positive feedback and thereby led to delayed and persistent inflammation in the injured wound, which caused an aberrant healing response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Besides, a previous report also suggested that senescent cells could disable the efferocytosis function of macrophages to enable their coexistence within the tissue milieu. [ 41 ] Therefore, we could propose that crosstalk between senescent cells and pyroptotic macrophages might result in positive feedback and thereby led to delayed and persistent inflammation in the injured wound, which caused an aberrant healing response.…”
Section: Discussionmentioning
confidence: 99%
“…YARS down-regulation did not modify p21 level but significantly increased p15 expression in MCF7 cells but not in LS174T cells (Figure 1E and Supplementary Figure 1C, note that p16INK4 is inactivated in the two cell lines). We and others have recently shown that senescent cells can be identified by an increased expression of the CD47 receptor (12,17). Results presented Figure 1F indicate that YARS inhibition led to a significant increase in the number of CD47 high MCF7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the present study we examined the overall adherent lung myeloid population isolated from human lung explants without distinguishing between satiated (i.e., CD11b low phenotype) or activated (i.e., CD11b high phenotype). Schloesser D et al (Schloesser et al, 2023) showed that a suppressed macrophage phenotype was mediated through a cell contact-dependent interaction with senescent fibroblasts. While our results indicate that primary IPF and PASC fibrosis myeloid cells showed an intrinsic suppression of myeloid cell activity, future studies will address the role of the senescent environment on the impairment of IPF and PASC-F lung myeloid cells and whether LTI-2355 alters the functionality of these myeloid cells such that these cells exhibit a pro-resolving phenotype (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%